Daun Kelor (Moringa Oleifera) Membantu Mengatasi dan Mencegah Anemia Pada Remaja - Sri Widayati, Rina; Wulandari, Riyani; Fatmawati, Siti; Sari, Dewi Kartika; Khotimah, Nurul (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
Background : Adolescents need a lot of nutrients because of their rapid growth period. They are prone to anemia, especially iron deficiency anemia. It can increase hemoglobin levels by boiling Moringa leaves, which have nutritional levels of iron 5 times higher than spinach. Objective : To determine the effect of hemoglobin levels in female adolescents before and given Moringa leaf extract. Methods : The design of this study was quantitative with a one-group pre-test and post-test design. The purposive sampling method was used in the sampling process. As many as 29 respondents were young women who experienced anemia. To carry out the intervention, the boiled water of Moringa leaves was drunk consecutively for 2 weeks (14 days) with a dose of 2 times a day, which was taken every morning and every evening. Results : From the Wilcoxon test showed that there was a significant effect between before and after administration of Moringa leaf extract because the p value <0.05. Conclusion : This study found that the intervention of Moringa leaf extract had an effect on increasing hemoglobin levels in female adolescents.